Stable Isotopes Trace the Truth: From Adulterated Foods to Crime Scenes - Ehleringer, James R. (2015)
Stable isotopes are valuable biogeochemical markers for solving problems faced by society today, such as distinguishing authentic from adulterated foods and beverages or tracing the origins of illicit drugs. Hydrogen and oxygen isotopes in water exhibit distinct continental patterns (isoscapes), which provide useful region-of-origin information. We ourselves reflect the stable isotope ratios of the water we drink and the food we eat: our hair records any isotopic changes to our diets, which can often be related to location. This latter aspect can be of interest to law enforcement in determining the origins and travel histories of unidentified murder victims.